Design and validation of a participatory environment questionnaire in elementary education - Rangel Ledezma, Yunuen Socorro; Arzola-Franco, David Manuel; González Ortiz, Ana María (Avances en Supervisión Educativa, 2019)
The aim of this research is to design and analyze the validation of content and construct for internal relations, of a questionnaire on participatory climate applied to teachers of primary education institutions in three dimensions: socio-affective, socio-political and organizational. Knowing the interaction in schools, as well as the effect of the Technical School Council (CTE). The content validation was carried out through the analysis of six experts by using the Delphi technique; The validity of the construct was determined by analyzing the application of the questionnaire to 493 teachers from different primary schools in Aguascalientes, Veracruz and Chihuahua, who analyzed the quality and format of the questions. The questionnaire included 45 questions, adjusted for the presence of content and construct validity. The exploratory and confirmatory factor analysis indicated the three initial dimensions, but the number of questions and the accommodation differed to what was proposed at the beginning of the study.
Keywords: structural adjustment; educational organization; measure instrument; assessment